Effect of temporal frequency on habituation in migraine. (10th March 2023) - Sharp, Alex; Föcker, Julia; O'Hare, Louise
Abstract: Individuals with migraine tend to experience discomfort when viewing flickering stimuli. It has been suggested that one of the characteristics of migraine is a lack of habituation to repetitive visual stimuli, although findings can be mixed. Previous work has typically used similar visual stimuli (chequerboard) and only one temporal frequency. This study systematically varied the spatial and temporal characteristics of the visual stimulus, using steady‐state visual evoked potentials to assess the differences in amplitude between migraine and control group over consecutive blocks of stimulation. Twenty individuals with migraine and 18 control observers were asked to rate their visual discomfort after viewing sequences of flickering Gabor patches with a frequency of either 3 or 9 Hz across three different spatial frequencies (low 0.5 cpd; mid‐range 3 cpd; high 12 cpd). Compared to the control group, the migraine group showed a reduction in SSVEP responses with increased exposure, suggesting habituation processes are intact at 3‐Hz stimulation. However, at 9‐Hz stimulation, there was evidence of increased responses with increasing exposure in the migraine group in particular, which might suggest a build‐up of the response over repetitive presentations. Visual discomfort varied with spatial frequency, for both 3‐ and 9‐Hz stimuli, the highest spatial frequencies were the least uncomfortable compared to the low‐ and mid‐range spatial frequencies in both groups. This difference in SSVEP response behaviour, dependent on temporal frequency, is important to consider when researching the effects of repetitive visual stimulation in migraine and could give some indication of build‐up of effects leading to aversion to visual stimuli. Abstract : We measured SSVEP responses in migraine and control groups to grating stimuli that varied in spatial and temporal frequencies. Compared to control groups, slower frequencies seem to result in intact habituation processes, faster frequencies resulted in increased responses in those with migraine over time. The mid‐range spatial frequency stimuli were reported to be the most uncomfortable in both groups.